The most common dermatoses of athletes - Szot, Anna; Kmak, Bożena; Górska, Magdalena (Journal of Education, Health and Sport, 2024)
Introduction and purpose The skin and subcutaneous tissue constitute the body's protective barrier. It also fulfills important physiological functions. It protects internal organs against the harmful effects of environmental factors and maintains the balance between the human body and the environment. Athlete's dermatoses are a wide group of skin diseases that may occur as a result of specific conditions to which people who practise sports are exposed. Some skin diseases are characteristic of specific sports, while others may occur regardless of the type of physical activity performed. Mechanical damage to the epidermis, excessive humidity, contact with pathogens and exposure to various environmental factors play a key role in the development of these diseases. Regular dermatological check-ups are crucial for identifying and treating skin lesions and preventing mass infections caused by infectious agents. The study discusses the most common dermatoses in athletes, including fungal, bacterial and viral infections, contact dermatitis and dermatoses caused by mechanical and environmental factors. Materials and methods The literature included in the PubMed, BioMed Central and Polish Medical Platform databases is searched by means of the words such as dermatosis, sport, skin, fungal, bacterial, viral infection, contact dermatitis. Quoted sources in selected works were also used. Conclusions Many factors can have a harmful effect on the skin, negatively affect its function as an integral barrier of the body and, consequently, cause the development of dermatoses, which are quite common among athletes due to frequent contact with sweat, clothing, sports equipment and the environments in which they train. Prevention is an important element in minimizing the risk of skin problems and this is key to maintaining health and continuing physical activity.